Blended Learning in English Teaching and Learning: A Review of the Current Literature - Albiladi, Waheeb S.; Alshareef, Khlood K. (Journal of language teaching and research, 2019)
This paper provides a review of the research related to the use of blended learning in English as a second/foreign language context. Blended learning is a relatively new field that combines traditional teaching approaches with distance and online learning. The use of blended learning has been emphasized by the recent research that examines the academic and social benefits of this teaching approach. Because it combines traditional and online teaching modes, the promise of blended learning rests on the strengths of both teaching approaches. The present review of the literature revealed that blended learning can be used effectively to develop language skills, enhance the English learning environment, and promote students’ motivation toward learning the language. There is a dearth of literature that examines the challenges that face language teachers when using blended learning. Hence, more research has to be done to identify and deal with these challenges.